History of Aircraft Construction (Former Tashkent Aviation Factory) - Sharipkhojaevic, Tukhtabaev (Indonesian Journal Publisher, 2025)
This article covers the history of the former Tashkent Aviation Factory. It covers information on the organization, activities of the factory, information about aircraft produced during the Soviet period, information on the works carried out by the factory, the used transports, the main products of the factory, technological achievements, its state after the independence, reorganization, contribution to the aviation, industry and engineering of Uzbekistan.